Just another niche in the wall? How specialization is changing the face of mainstream economics. (10th July 2017) - Cedrini, Mario; Fontana, Magda
Abstract: There is considerable discussion on so-called 'mainstream pluralism', that is, on the co-presence of a variety of research programmes in today's mainstream economics that: 1. significantly deviate from the neoclassical core; 2. are pursued by different, often separate communities of researchers; and 3. have their origins outside economics. The literature tends to regard mainstream pluralism as a transitory state towards a new, post-neoclassical, mainstream. This paper advances a new interpretation: it suggests that the changing and fragmented state of mainstream economics is likely to persist over time under the impact of specialization (as a self-reinforcing mechanism) and the creation of new specialties and approaches, also through collaboration with researchers from other disciplines.